Tribological properties of twin wire arc spray coated aluminum cylinder liner. (5th November 2015) - Kim, Jae-Kang; Xavier, Fabio-Antonio; Kim, Dae-Eun
Abstract: The effects of honing process on the friction and wear behaviors of Twin Wire Arc Spray (TWAS) coated aluminum cylinder liners were investigated using a pin-on-reciprocating type of a tribotester. Two types of coated cylinder liners were prepared for the tests: Type I — smooth honing (SH) with 40° honing angle, and Type II — helical structure honing (HSH) with 140° honing angle. The aluminum cylinder liners were coated with an Fe0.8C wire by the TWAS process. In un-lubricated condition, Type II specimen showed lower coefficient of friction (COF) compared to Type I specimen. This result was due to the fact that the groove of Type II was sufficiently large to trap the wear particles that may otherwise contribute to three body abrasive wear. In lubricated condition, Type I showed lower COF due to its lower roughness in comparison to Type II. The experimental results indicate that TWAS process can be effectively utilized for engine applications in conjunction with optimum honing process for the cylinder liner. Graphical abstract: Highlights: Aluminum cylinder liners were coated by Twin Wire Arc Spray process. Effects of smooth and helical structure honing processes were assessed. HSH liner showed better frictional characteristics under un-lubricated conditions. SH liner showed better frictional characteristics under lubricated conditions. TWAS coated aluminum liners with optimum honing process were proposed.